Expression of cytochrome P450 epoxygenases and soluble epoxide hydrolase is regulated by hypolipidemic drugs in dose-dependent manner - Cizkova, Katerina (Toxicology and applied pharmacology, 2018)
CYP epoxygenases metabolize arachidonic acid into four regioisomers of epoxyeicosatrienoic acids (EETs) which are hydrolysed into their corresponding diols by soluble epoxide hydrolase (sEH). EETs are very biologically active molecules. They promote proliferation and inhibit apoptosis as well as numerous other functions within organisms. Peroxisome proliferator-activated receptor α (PPARα) play role in regulation of CYP epoxygenases and sEH. PPARα is the ligand-dependent transcriptional factor which is activated by various compounds, including fibrates. The latter are widely used in clinical practice. This study investigates the changes in expression of CYP2C8, CYP2J2, and sEH in HEK293, HepG2, and HT-29 cell lines after fibrate treatment using two different incubation times. The results demonstrate that the effect of fibrates on arachidonic acid-metabolizing enzymes expression is concentration-dependent. Although CYP2C8 expression is downregulated by the fibrates treatment, the results reveal that changes in CYP2J2/sEH ratio are closely associated with cell proliferation and could explain the differing proliferation response of cells to different concentrations of fibrates.
Keywords: Dose-Response Relationship, Drug; vztah mezi dávkou a účinkem léčiva; regulace genové exprese enzymů; systém (enzymů) cytochromů P-450; buňky Hep G2; Fibrates; HEK293 Cells; HT29 Cells; Arachidonic Acids; epoxid hydrolasy; kyseliny arachidonové; Hep G2 Cells; PPAR alpha; Cytochrome P-450 Enzyme System; hypoglykemika; Fibric Acids; buňky HT-29; cytochrom P450 CYP2C8; Soluble epoxide hydrolase; HEK293 buňky; Humans; Cytochrome P-450 CYP2J2; cytochrom P-450 CYP2J2; Gene Expression Regulation, Enzymologic; Cytochrome P-450 CYP2C8; Peroxisome proliferator-activated receptor alpha; Proliferation; deriváty kyseliny fibrové; CYP epoxygenases; Hypoglycemic Agents; Epoxide Hydrolases; PPAR alfa; lidé; Protein expression